Abdominal cocoon: a rare presentation of abdominal distension in a young adult male—a case report - Naheed Habibullah; Hassan, Syed; Afzal Khan, Badar; Najm Us Sahar (Journal of the Pakistan Medical Association, 2025)
This case report outlines the presentation, evaluation, and management of a 35-year-old male patient with a history of subacute intestinal obstruction, who presented with generalised abdominal pain and distension. Clinical evaluation revealed a tender supraumbilical mass, and imaging confirmed abdominal cocoon—a rare condition where small bowel loops are encapsulated by a thin peritoneal layer. Initially managed conservatively, the patient’s condition improved and he was discharged from the hospital but later returned with recurrent intestinal obstruction. Subsequently, he underwent exploratory laparotomy with open adhesiolysis, which was successful without any post-operative complications. The patient has since been stable during the follow-up period, showing good tolerance to treatment. Keywords: Abdominal cocoon, Abdominal distension, Peritoneal encapsulation, Conservative management.